2016
DOI: 10.1002/chem.201504950
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Aggregation and Toxicity of a Tau‐Derived Peptide using Its Glycosylated Analogues

Abstract: Protein glycosylation is a ubiquitous post-translational modification that regulates the folding and function of many proteins. Misfolding of protein monomers and their toxic aggregation are the hallmark of many prevalent diseases. Thus, understanding the role of glycans in protein aggregation is highly important and could contribute both to unraveling the pathology of protein misfolding diseases as well as providing a means for modifying their course for therapeutic purposes. Using β-O-linked glycosylated var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 71 publications
(34 reference statements)
1
35
0
Order By: Relevance
“… 48 , 49 For example, it has recently been shown that O -glycosylated tau-derived peptides can selectively inhibit aggregation and toxicity of wild type tau variants. 50 Triggered by the results of our ThT fluorescence assay, we tested if homogeneously PEGylated PrPs can inhibit fibril formation of unmodified wt PrP. To this end, we mixed wt PrP with homogeneously PEGylated PrP variants in molar ratios of 1 : 1, 5 : 1 and 10 : 1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 48 , 49 For example, it has recently been shown that O -glycosylated tau-derived peptides can selectively inhibit aggregation and toxicity of wild type tau variants. 50 Triggered by the results of our ThT fluorescence assay, we tested if homogeneously PEGylated PrPs can inhibit fibril formation of unmodified wt PrP. To this end, we mixed wt PrP with homogeneously PEGylated PrP variants in molar ratios of 1 : 1, 5 : 1 and 10 : 1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Elucidating the structure and formation mechanism of amyloid fibrils is of paramount importance for current structural biology . However, the limited order of fibrils isolated from diseased tissues, as well as their great morphological diversity, have limited their atomic‐level structural determination.…”
Section: Introductionmentioning
confidence: 99%
“…The VQIVYK peptide, termed PHF6, is a highly aggregative short segment located in the third repeat of the MT-binding region of the tau protein [17,18], which can assume the β-sheet structures necessary for the aggregation of tau into oligomers and NFTs [17,19]. This peptide is widely used as a model for studying tau aggregation and examining candidate inhibitors [20,21,22,23,24,25,26]. …”
Section: Introductionmentioning
confidence: 99%